Further optimization of the M(5) NAM MLPCN probe ML375: Tactics and challenges - Kurata, Haruto (Bioorg Med Chem Lett, 2014)
This letter describes the continued optimization of the MLPCN probe ML375, a highly selective M(5) negative allosteric modulator (NAM), through a combination of matrix libraries and iterative parallel synthesis. True to certain allosteric ligands, SAR was shallow, and the matrix library approach highlighted the challenges with M(5) NAM SAR within in this chemotype. Once again, enantiospecific activity was noted, and potency at rat and human M(5) were improved over ML375, along with slight enhancement in physiochemical properties, certain in vitro DMPK parameters and CNS distribution. Attempts to further enhance pharmacokinetics with deuterium incorporation afforded mixed results, but pretreatment with a pan-P450 inhibitor (1-aminobenzotriazole; ABT) provided increased plasma exposure.